Aprendizagens de professores da educação infantil de conceitos geométricos tendo o origami como material com vistas ao desenvolvimento de práticas de ensino - Presse, Priscila Marçal (2022)
This dissertation aimed to analyze the learning of early childhood education teachers about geometric concepts using origami as a playful and didactic material with a view to the development of teaching practices. This research was driven by the following question: what are the learnings of early childhood education teachers about geometric concepts when they use origami in the context of an online course? To answer this question, substantiate and support this dissertation, the Historical-Cultural Theory was used, in which Vygotsky seeks to show that human knowledge derives from social relations with the use of language and signs. The methodology was qualitative and the data were obtained from the analysis of episodes that are characterized from the subject's speech, gestures and action. The methodology is qualitative. Origami was used as didactic material in order to enable learning about the teaching of geometric concepts in the context of early childhood education, based on experiences that took place among teachers, in a context of continuing education. The empirical material was compiled from a bibliographic survey and experiences that occurred during the development of an online course that was offered to Early Childhood Education teachers, from August to October 2021, together with the Municipal Secretary of Education in a municipality located in the interior of the state of São Paulo. Google Meet platform was used to teach classes and Google Classroom to send and receive problem situations involving origami, since, at that moment, we were in a pandemic context. The analyzes of the learning were carried out based on the following categories: 1) Learning that took place during the teachers' interactions when performing the folds: difficulties and facilities; 2) Learning that considers the recognition of geometric figures in the composition and decomposition of origami and 3) Learning that occurred during the recognition of geometric concepts in the composition and decomposition of origami. Based on these categories, it was possible to observe that teachers enrolled in this course because they considered the topic presented to be interesting and because they wanted to learn how to make origami, as well as discovering different ways to use it in the classroom. In other words, they wanted to learn how to use origami as a playful and didactic material during their classes. At first, we emphasize that, during the presentation of possible geometric concepts, among them the composition and decomposition of geometric figures that can be approached with origami, some teachers were reluctant to participate in the discussions in the virtual class because they did not remember of the mathematical concepts that would be addressed. The research shows that origami is a great material to be used by the kindergarten teacher in their teaching practice in the classroom to achieve the learning of figures and geometric concepts, and origami allows the student to learn geometry and develop it skills you will use throughout your life. It should also be considered that the proposal of the extension course is configured as an educational product of this dissertation.